Comparative efficacy and safety of multimodality treatment for advanced hepatocellular carcinoma with portal vein tumor thrombus: patient-level network meta-analysis - Leung, John Hang; Wang, Shyh-Yau; Leung, Henry W. C.; Chan, Agnes L. F. (Frontiers in Oncology, 2024)
Background: Portal vein tumor thrombus (PVTT) is a common complication and an obstacle to treatment, with high recurrence rate and poor prognosis. There is still no global consensus or standard guideline on the management of HCC with PVTT. Increasing evidence suggests that more aggressive treatment modalities, including transarterial chemoembolization, radiotherapy, targeted therapy, and various combination therapies, may improve the prognosis and prolong survival of aHCC patients with PVTT. Therefore, we aim to comprehensively review and compare the efficacy and safety of these advanced options for the treatment of aHCC with PVTT.Methods: A comprehensive literature search was conducted on PubMed, EMBASE for phase II or III randomized controlled trials (RCTs) investigating multimodality treatments for aHCC with PVTT. Kaplan-Meier curves for overall survival (OS) and progression free survival were reconstructed to retrieve individual patient-level data to strengthen the benefit comparison of all the interested multimodality treatments. Each study was pooled in a fixed-effects network meta-analysis (NMA). NMAs were also conducted using study-level HRs for various subgroups, including viral etiology, Barcelona Clinic Liver Cancer (BCLC) staging, alpha-fetoprotein (AFP) levels, macrovascular invasion or portal vein tumor thrombosis, and extrahepatic spread. Treatment strategies were ranked using SUCRA scores.We identified 16 randomized controlled trials that met inclusion criteria. Among them, 5236 patients had OS results, and 5160 patients with PFS were included in the analysis. Only hepatic arterial infusion chemotherapy of fluorouracil, leucovorin, and oxaliplatin (HAIC-FO) showed OS and PFS benefit over all other therapies. In terms of OS, HAIC-FO, nivolumab and TACE+Len were superior to sorafenib , lenvatinib and donatinib monotherapy as well as HAIC-FO+ Sor. For PFS, TACE+Len showed better PFS benefit than lenvatinib, donatinib and tremelimumab+durvalumab. Low heterogeneity (I 2 <50%) and no inconsistency was observed.The Sucra score for OS ranked HAIC-FO+Sorfenib as the best treatment option among all multimodality treatments and in hepatitis B, MVI or PVTT with EHS and AFP 400 μg/L subgroups.Conclusion: HAIC-FO and HAIC-FO+ Sorafenib were statistically better options for unresectable hepatocellular carcinoma with MVI or PVTT among the multimodality treatments.